Topics in Theoretical Computer Science: Second IFIP WG 1.8 International Conference, TTCS 2017, Tehran, Iran, September 12-14, 2017, Proceedings - Mousavi, Mohammad Reza; Sgall, Jiri (Lecture Notes in Computer Science, 2017)
This book constitutes the refereed proceedings of the Second IFIP WG 1.8 International Conference on Topics in Theoretical Computer Science, TTCS 2017, held in Tehran, Iran, in September 2017. The 8 papers presented in this volume were carefully reviewed and selected from 20 submissions. They were organized in topical sections named: algorithms and complexity; and logic, semantics, and programming theory.